Predation rate of Thrips tabaci larvae by Neoseiulus cucumeris is influenced by prey density and presence of a host plant - Nielsen, M-C.; Davidson, M.M.; Butler, R.C. (New Zealand Plant Protection, 2014)
Prey consumption rate by natural enemies may be affected by the preys host plant and prey density The predation rate of the mite Neoseiulus cucumeris at different densities of firstinstar Thrips tabaci larvae in the presence (onion) or absence (green plastic) of a host was measured In the first experiment using a disc bioassay N cucumeris exhibited a typeII densitydependent functional response to prey on both disc types Prey consumption was reduced on onion relative to plastic A second experiment using onion bulbs and green plastic bulbs indicated a decrease in the consumption rate on plastic bulbs compared with plastic discs The survival or recapture of N cucumeris on onion bulbs was less than 7 and no prey consumption data were obtained The results indicate that onion as a host plant has a negative effect on consumption of T tabaci by N cucumeris and on survival of the predator mite